Strategy for Preservation and Development of Legend-Based Tourism Interest through the Preparation of Web-Assisted Literacy Media - Yostiani Noor Asmi Harini; Jatmika Nurhadi; Dina Siti Logayah (CV. Creative Tugu Pena, 2024)
The changing context of legend narration and the difficulty of accessing legends are the background of legend preservation efforts. The purpose of this study is to describe the right strategy to preserve legends in accordance with the characteristics of the next generation and to utilize legends in the development of literary tourism interest. The theories used in this research are folklore and literary tourism. The method used in this research is the research and development model. This research is expected to contribute in the form of strategies that can be used to preserve legends as Indonesian cultural wealth that contains local wisdom. In addition, this research product is expected to develop interest in literary tourism in order to increase the independence, progress and competitiveness of the nation.